Aggravation of nonalcoholic steatohepatitis by moderate alcohol consumption is associated with decreased SIRT1 activity in rats - Nascimento, André F. [UNESP]; Blanche C.; Luvizotto, Renata A. M. [UNESP]; Seitz, Helmut K.; Wang, Xiang-Dong (Hepatobiliary Surgery And Nutrition, 2013)
Chronic alcohol intake decreases adiponectin and sirtuin 1 (SIRT1) expressions, both of which have been implicated in various biological processes including inflammation, apoptosis and metabolism. We have previously shown that moderate consumption of alcohol aggravates liver inflammation and apoptosis in rats with pre-existing nonalcoholic steatohepatitis (NASH). This study investigated whether moderate alcohol intake alters SIRT1 activity, adiponectin/Adiponectin receptor (AdipoR)-related signaling and lipid metabolism in a pre-existing NASH status. Sprague-Dawley rats were fed with a high-fat diet (71% energy from fat) for 6 weeks to induce NASH then subsequently divided into 2 sub-groups: fed either a modified high-fat diet (HFD, 55% energy from fat) or a modified high-fat alcoholic diet (HFA, 55% energy from fat and 16% energy from ethanol) for an additional 4 weeks. We observed in comparison to HFD group, HFA increased hepatic nuclear SIRT1 protein but decreased its deacetylase activity. SREBP-1c protein expression and FAS mRNA levels were significantly upregulated, while DGAT1/2 and CPT-I mRNA levels were downregulated in the livers of HFA compared to HFD. Although hepatic AdipoR1 decreased, HFA did not alter AdipoR2 and their downstream signaling. There were no significant changes in plasma adiponectin and free fatty acids (FFA), as well as adiponectin expression in adipose tissue between the two groups. The present study indicates that suppression in SIRT1 deacetylase activity contributes to alcohol-exacerbated hepatic inflammation and apoptosis in rats with pre-existing NASH. In addition, moderate alcohol intake did not modulate adiponectin/AdipoR signaling axis in this model.
Keywords: Adiponectin; Alcohol consumption; Nonalcoholic steatohepatitis (nash); Rats; Sirtuin-1 (sirt1)